2014
DOI: 10.1017/jfm.2014.167
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure interaction of a square cylinder at different angles of attack

Abstract: This study investigates the free transverse flow-induced vibration (FIV) of an elastically mounted low-mass-ratio square cylinder in a free stream, at three different incidence angles: α = 0 • , 20 • and 45 • . This geometric setup presents a body with an angle of attack, sharp corners and some afterbody, and therefore is a generic body that can be used to investigate a wide range of FIV phenomena. A recent study by Nemes et al. (J. Fluid Mech., vol. 710, 2012, pp. 102-130) provided a broad overview of the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
126
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 34 publications
24
126
4
Order By: Relevance
“…At m * = 5.78, the upper branch covers the range U * = 4.8-6.4; the lower response branch lies within the range 6.4 U * 9.5; and the desynchronised region occurs for U * > 9.5. Previous studies by Khalak & Williamson (1997) and Zhao et al (2014b) at m * = 2.4 showed a peak amplitude response of A * ≈ 0.95. The mean of the highest 10 % of peak amplitude response (A * 10 ) of the current system is A * 10 = 0.82.…”
Section: Validationmentioning
confidence: 79%
See 3 more Smart Citations
“…At m * = 5.78, the upper branch covers the range U * = 4.8-6.4; the lower response branch lies within the range 6.4 U * 9.5; and the desynchronised region occurs for U * > 9.5. Previous studies by Khalak & Williamson (1997) and Zhao et al (2014b) at m * = 2.4 showed a peak amplitude response of A * ≈ 0.95. The mean of the highest 10 % of peak amplitude response (A * 10 ) of the current system is A * 10 = 0.82.…”
Section: Validationmentioning
confidence: 79%
“…The vibration response of a non-rotating circular cylinder undergoing VIV is compared against previous work by Khalak & Williamson (1997& Williamson ( , 1999 and Zhao et al (2014b) in figure 4 . F igure 4 (a) p resents t he a mplitude r esponse a s a f unction o f reduced velocity and shows the current experimental configuration p roduces n on-rotating VIV results in good agreement with previous VIV studies.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the circular cylinder, other prisms such as square prism and triangular prism also presented VIV responses. Nemes et al [10,11] reported that the incident angle had a significant influence on the performance of square prisms. When the incident angle was 45 degrees (diamond cross-section), the square prism presented a self-limited motion (which was VIV).…”
Section: Introductionmentioning
confidence: 99%